1990
DOI: 10.1002/elan.1140020506
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical NO2 gas sensors: Model and mechanism for the electroreduction of NO2

Abstract: Two types of sensing devices have been studied in order to elucidate the mechanism of response of amperometric gas sensors. A high-surface-area electrode (HSAE) sensor produces fast electrode reactions, and the steady-state sensor signals are controlled either by permeation or by the supply of analyte to the sensor. For low-surface-area electrode (LSAE) sensors, a kinetically controlled signal is observed. A mechanism that involves a "chemically" induced changes in the gold electrode surface oxide coverage is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0
1

Year Published

1992
1992
2018
2018

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 56 publications
(23 citation statements)
references
References 16 publications
0
22
0
1
Order By: Relevance
“…The detection of nitrogen dioxide by amperometric sensors with polymer electrolytes is relatively well known and particular redox reactions on the working and counter electrodes have been described in the literature [ 31 , 32 ]. This work is focused on the systematic study concerning key sensor parameters for the five ionic liquids mentioned above.…”
Section: Resultsmentioning
confidence: 99%
“…The detection of nitrogen dioxide by amperometric sensors with polymer electrolytes is relatively well known and particular redox reactions on the working and counter electrodes have been described in the literature [ 31 , 32 ]. This work is focused on the systematic study concerning key sensor parameters for the five ionic liquids mentioned above.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that the presence of NO can interfere with methane oxidation under atmospheric conditions, because there occurs oxidation of NO (NO to NO + ) at positive potentials in ILs and NO is easily oxidized to NO 2 . 45 Although it was difficult to observe clearly the oxidation peak of NO in [C 4 mpy][NTf 2 ], the NO oxidation peak likely overlaps with the methane oxidation peak if they are mutually present. The influence of NO was decreased by the presence of oxygen, which is likely a result of NO quickly reacting with O 2 at room temperature to form NO 2 .…”
Section: Resultsmentioning
confidence: 99%
“…All the measurements were carried out at 25 ± 3 • C. The reaction of NO 2 by this type of sensor has been considered as the formula (1) [8][9][10].…”
Section: Methodsmentioning
confidence: 99%